Cognitive Involvement in Balance, Gait and Dual-Tasking in Aging: A Focused Review From a Neuroscience of Aging Perspective - Li, Karen Z. H.; Bherer, Louis; Mirelman, Anat; Maidan, Inbal; Hausdorff, Jeffrey M. (Frontiers in Neurology, 2018)
A substantial corpus of evidence suggests that the cognitive involvement in postural control increases with aging. A large portion of such studies were based on dual-task experimental designs, which typically use the simultaneous performance of a motor task (e.g., static or dynamic balancing, walking) and a continuous cognitive task (e.g., mental arithmetic, tone detection). This focused review takes a cognitive neuroscience of aging perspective in interpreting cognitive motor dual-task findings. Specifically, this review considers the importance of identifying the neural circuits that are engaged by the cognitive task in relation to those that are engaged during motor task performance. Following the principle of neural overlap, dual-task interference should be greatest when the cognitive and motor tasks engage the same neural circuits. Moreover, the literature on brain aging in general, and models of dedifferentiation and compensation, in particular, will be applied to the extant findings on aging and dual-task postural control. Also considered is the concept of multisensory aging, and the degree to which the age-related decline of other systems (e.g., vision, hearing) contribute to cognitive load. Finally, recent work on focused cognitive training, exercise and multimodal training of older adults and their effects on postural outcomes will be reviewed. In keeping with the principle of neural overlap, the training studies will be discussed in terms of the neural underpinnings of training-related improvements to postural control, and what is known about the efficacy and optimization of cognitive training in older adults.